Substituição isomórfica de Al 3+ por Sb 3+ em Hidróxidos Duplos Lamelares (HDLs) visando uma alternativa à quimioterapia da leishmaniose - Silva, Tamires Andrade da (2020)
Among the nanocarriers, the Layered double hydroxides (LDHs), for having a simple and flexible structure due to the possibility of varying the nature of the di and trivalent cations in their composition, and allowing the intercalation of anionic species, have attracted the interest of several researchers. Antimony (Sb) and its compounds have been known and used since antiquity, for therapeutic purposes they have been used in leishmaniasis chemotherapy, and even being considered drugs of first choice, they have some significant disadvantages, among them, the incidence of side effects toxic. Therefore, a series of substances have been researched regarding the leishmanicidal action, in this sense, the synthesis of MgAl-LDHs with isomorphic substitution of aluminum for antimony, emerges as a potential compound to be used in this treatment. Therefore, the substituted products and the respective precursors, for comparison purposes, were synthesized through co-precipitation without and with hydrothermal treatment, and as variables were analyzed: molar ratio M 2 + / M3 + (2: 1; 3: 1 and 4:1), and drying technique (conventional drying, lyophilization, spray drying). Colloidal suspensions from synthesis with hydrothermal treatment were evaluated by Dynamic light scattering (DLS), and powders from drying were first analyzed by Powder X-Ray Diffraction (PXRD), and after confirmation of substitution in the products, they were selected for the analysis of Energy Dispersive X-ray Detector (EDX), Hydride generation atomic fluorescence spectrometry (HGAFS), Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetry (TGA) and Scanning Electron Microscopy (SEM). The structural evaluation showed that the synthesized products showed the diffraction reflections characteristic of an LDH, and through the calculation of the network parameters, it was possible to infer the successful incorporation of Sb3 + in the lamellae of 4 products (S7, S11, S14, S17) , and by the HG AFS technique it was possible to obtain the quantification of Sb in the products, 3.08; 1.36; 0.81 and 1.65%, respectively. The FTIR results indicated that all bands that characterize the LDH pattern were present, and the similarities between the thermograms obtained from the TGA again confirm the similar structure of the prepared solids. The release profile of Sb in all products was marked by two stages, and the synthesis method had an influence on this release. Therefore, we can confirm that the replacement LDHs have been obtained, and that they may represent a new approach in the treatment of leishmaniasis.